A DISCRETE CHAOTIC ENCRYPTION ALGORITHM USING LORENZ ATTRACTOR (International Journal of Engineering and Computer Science, 2013)
This Communication of critical information over global computer network needs encrypting the digital information before transmitting through the network. In this research article, a novel idea is proposed for a Discrete Chaotic Data encryption/decryption Algorithm using Lorentz attractors. The encryption system consists of a chaos generator, which takes the input message as the plain text and produces an independent output message known as cipher text. In the present approach the data to be transmitted is digitally modified by the chaotic system to produce the cipher text, which is sent through the transmission medium and the reverse process occurs at the reception end to decrypt the data. The essence of the present procedure is to use complex dynamics but simple mathematical descriptions and algorithms of chaotic systems for the purpose of encryption. The combination of these techniques results in a system that is extremely simple to implement, yet results cryptographically very robust. Also it will be highly resistive to differential and statistical attacks. The algorithm is independent of the data size to be encrypted and has been verified for several sets of input data consisting of all allowable characters. A preliminary test is also made to check the strength of the key and the results are very encouraging. Several analysis is been carried out to validate the strength, arbitrariness and the entropy of this newly proposed algorithm.